Productivity of a harvesting operation for a small clear-cut block by direct grappling using a processor in the Kochi University Forest. Issue 3 (2nd September 2019) - Suzuki, Yasushi; Kusaka, Haruka; Yamaguchi, Yuki; Aoki, Haruka; Hayata, Yoshifumi; Nagai, Hirotaka
ABSTRACT: A case study was analyzed on productivity of clear cutting conducted by novel logging machines in the Kochi University Forest. A small block (0.15 ha in average) has been clear-cut annually to prepare a practice planting site for the Forest Science Course students. Until 2015, harvesting operations were performed by a small-scale system, such as a winch-mounted mini-forwarder. However, in 2016 an updated system was introduced with a processor head equipped on a base machine of 0.25 m 3 bucket size-class and a forwarder with a 3 t loading capacity. A series of operations was conducted with this new system in November 2016, including cutting, logging, processing, bucking, and forwarding. The total productivity was evaluated at over 4 m 3 /person-day, a significant increase over the former system, at 2 m 3 /person-day. A critical factor in productivity was extraction by the processor, which was affected by the angle of felled trees relative to a strip road.